Recent development of repairable, malleable and recyclable thermosetting polymers through dynamic transesterification - Liu, Tuan; Zhao, Baoming; Zhang, Jinwen (Polymer (Guilford), 2020)
A fully polymerized (cured) thermoset is no longer capable of flow like a thermoplastic to be recycled and reprocessed into a new object. Developing repairable, malleable and recyclable thermoset is necessary to reduce the ever-increasing polymer waste as well as to extent the service life of the existing polymer materials. As a new class of “recyclable” and/or “reprocessable” crosslinked polymer, “vitrimers” have just emerged in the recent decade. Vitrimers are permanently crosslinked polymers based on dynamic covalent networks. Such networks are stable at the service temperature yet become labile and reprocessable at elevated temperatures due to stimulus activated bond-exchange reactions. Because vitrimers combine the advantages of both thermosets and thermoplastics, they have received extensive attention. There are many vitrimer chemistries that have been reported. In this review, the discussion is focused on the developments of vitrimers based on dynamic transesterification reaction (DTER) between hydroxy groups and ester bonds, which is one of the most representative vitrimer chemistries. This review mainly includes the discussions of synthetic methods, vitrimer behaviors, application developments, and recycling methods. In addition, the challenges and outlook are also provided. [Display omitted]